Helicobacter pylori infection is associated with a reduced risk of developing eosinophilic oesophagitis. Issue 7 (22nd February 2016) - von Arnim, U.; Wex, T.; Link, A.; Messerschmidt, M.; Venerito, M.; Miehlke, S.; Malfertheiner, P.
Summary: Background: Eosinophilic oesophagitis (EoE) represents a chronic immune‐antigen‐mediated allergic disease of the oesophagus of still unknown aetiology. Environmental exposure has been postulated to play a pathogenetic role. Helicobacter pylori ( H. pylori ) infection has been inversely associated with allergic diseases including atopic dermatitis, asthma and allergic rhinitis and H. pylori may play a protective role in these conditions. Little is known about the relationship between EoE and H. pylori . Aim: To investigate in a case–control study whether H. pylori infection is associated with a reduced risk of developing EoE. Methods: H. pylori infection was evaluated by serology in 58 [11(19%) female, 47 (81%) male, median age: 36.5 years, range 20–72 years] patients with a clinical and histologically proven diagnosis of EoE and 116 age and sex‐matched controls (1 case: 2 controls). Antibodies against H. pylori were identified by enzyme‐linked immunosorbent assay. Patients with H. pylori ‐specific IgG ≥30 enzyme immunounits were classified as H. pylori ‐positive. Results: 3/58 (5.2%) patients with EoE had serological evidence of H. pylori infection (EoE – H. pylori current infection) and 5/58 (8.6%) reported prior eradication therapy for H. pylori infection (EoE – H. pylori former infection). The control group demonstrated significantly higher seroprevalence of H. pylori (37.9%, P < 0.0001) when compared to patients with EoE. EoE was inversely associated with H. pylori infection [odds ratio (OR) 0.24, 95% confidence interval (CI) 0.11–0.50]. Conclusion: Helicobacter pylori infection is inversely associated with EoE. Our results may contribute to further understanding the pathogenesis and evolving aetiology of EoE.